2013
DOI: 10.1037/a0033054
|View full text |Cite
|
Sign up to set email alerts
|

Key process issues in Cognitive Behavioral Analysis System of Psychotherapy (CBASP): Translation of an evidence-based model into clinical practice and training.

Abstract: Our "desired outcome" in writing this article was to present not only key process issues stemming from the Cognitive Behavioral Analysis System of Psychotherapy (CBASP; McCullough, 2000), but to highlight those therapy maneuvers that we, a "seasoned" clinician/supervisor and a clinical trainee, find most useful in delivering treatment and in conducting supervision. We strongly believe that it is only through the translation of evidence-based therapeutic models, such as CBASP, into effective training that a tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Complementing such outcome trials, though, process research on existing data can immediately help highlight factors that explain outcome variance in CBASP, which could inform modifications for improving this approach (Constantino et al, 2012). Perhaps the most logical starting point for such process analysis is the patient-therapist relationship given that it underscores all CBASP interventions; that is, CBASP theory posits that the patient–therapist relationship is central for supporting technique and/or promoting novel relational experiences necessary for interpersonal change (the main putative mechanism for how people become less depressed; McCullough, 2003; Vivian & Salwen, 2013). Supporting this perspective, a study using the Keller et al (2000) data found that early patient-rated therapeutic alliance quality (i.e., agreement on treatment goals and tasks in the context of a positive affective bond; Bordin, 1979) was associated with greater subsequent depression reduction after controlling for prior symptom change and multiple prognostically relevant patient characteristics (Klein et al, 2003).…”
mentioning
confidence: 99%
“…Complementing such outcome trials, though, process research on existing data can immediately help highlight factors that explain outcome variance in CBASP, which could inform modifications for improving this approach (Constantino et al, 2012). Perhaps the most logical starting point for such process analysis is the patient-therapist relationship given that it underscores all CBASP interventions; that is, CBASP theory posits that the patient–therapist relationship is central for supporting technique and/or promoting novel relational experiences necessary for interpersonal change (the main putative mechanism for how people become less depressed; McCullough, 2003; Vivian & Salwen, 2013). Supporting this perspective, a study using the Keller et al (2000) data found that early patient-rated therapeutic alliance quality (i.e., agreement on treatment goals and tasks in the context of a positive affective bond; Bordin, 1979) was associated with greater subsequent depression reduction after controlling for prior symptom change and multiple prognostically relevant patient characteristics (Klein et al, 2003).…”
mentioning
confidence: 99%
“…Within this model, therapists tend to use Contingent Personal Responsiveness to give patients feedbacks about the impact of their behaviors towards the therapist. These types of interventions are used to increase his/her insight (Vivian & Salwen, 2013).…”
Section: Introductionmentioning
confidence: 99%